A quarta revolução industrial e a inteligência artificial: um estudo sobre seus conceitos, reflexos e possível aplicação no Direito por meio da análise de texto jurídico como forma de contribuição no processo de categorização preditiva de acórdãos - Werner, Deivid Augusto (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation seeks to verify whether the law has determinant characteristics for the applicability of Artificial intelligence, through the analysis of specific aspects of the contemporary interrelationship between law and Artificial intelligence From the perspective of the so-called 4th Industrial Revolution, with observance in the present and the reflections in the future, whose objectives are presented through the weighting a) about the beginning of everything and state of the art ; b) regarding the perceived meaning of Artificial Intelligence, as well as ways of obtaining it (text mining, natural language processing, machine learning, algorithms and automated decision making); c) the possible impacts - perspectives and risks - of Artificial Intelligence in the legal arena. For this, the dissertation is divided into three parts, initially elucidating to jurists and non-jurists, about the characterization of the 4th Industrial Revolution and the reflexes of Artificial Intelligence, addressing the main concepts that permeate the theme, as well as those that say examples that have been used to understand the way Artificial Intelligence is obtained. The second part is directed to the analysis of the direct applicability of Artificial Intelligence in the Law, permeating already existing probabilities and models verified nowadays, despite the analysis of the risks and challenges inherent to the legal activity provided by the disruptive technologies. Finally, it is sought to reflect, methodologically, on an application of some of the concepts discreed in the context of the paper in a practical case, notably the "attributes" application – text mining that eventually became a "human dictionary", which represents the hypothesis of the dissertation, with the help of information technology tools, as well as external research carried out with Law professionals, thus enabling an understanding of what can be called the baseline of any one that is called Artificial Intelligence.
Keywords: 4ª Revolução Industrial; Inteligência Artificial; Novas Tecnologias; Mineração de Texto Jurídico; Direito; Advogado; 4th Industrial Revolution; Artificial intelligence; New technologies; Legal Text Mining; Law; Lawyer; ACCNPQ::Ciências Sociais Aplicadas::Direito